Optimal Lateral Row Anchor Positioning in Posterior-Superior Transosseous Equivalent Rotator Cuff Repair: A Micro–Computed Tomography Study. Issue 11 (22nd November 2016) - Zumstein, Matthias A.; Raniga, Sumit; Labrinidis, Agatha; Eng, Kevin; Bain, Gregory I.; Moor, Beat K.
Background: The optimal placement of suture anchors in transosseous-equivalent (TOE) double-row rotator cuff repair remains controversial. Purpose: A 3-dimensional (3D) high-resolution micro–computed tomography (micro-CT) histomorphometric analysis of cadaveric proximal humeral greater tuberosities (GTs) was performed to guide optimal positioning of lateral row anchors in posterior-superior (infraspinatus and supraspinatus) TOE rotator cuff repair. Study Design: Descriptive laboratory study. Methods: Thirteen fresh-frozen human cadaveric proximal humeri underwent micro-CT analysis. The histomorphometric parameters analyzed in the standardized volumes of interest included cortical thickness, bone volume, and trabecular properties. Results: Analysis of the cortical thickness of the lateral rows demonstrated that the entire inferior-most lateral row, 15 to 21 mm from the summit of the GT, had the thickest cortical bone (mean, 0.79 mm; P = .0001), with the anterior-most part of the GT, 15 to 21 mm below its summit, having the greatest cortical thickness of 1.02 mm ( P = .008). There was a significantly greater bone volume (BV; posterior, 74.5 ± 27.4 mm 3 ; middle, 55.8 ± 24.9 mm 3 ; anterior, 56.9 ± 20.7 mm 3 ; P = .001) and BV as a percentage of total tissue volume (BV/TV; posterior, 7.3% ± 2.7%, middle, 5.5% ± 2.4%; anterior, 5.6% ± 2.0%; P = .001) in the posterior third of the GT than in intermediate or anterior thirds. In terms of both BV and BV/TV, the juxta-articular medial row had the greatest value (BV, 87.3 ± 25.1 mm 3 ; BV/TV, 8.6% ± 2.5%; P = .0001 for both) followed by the inferior-most lateral row 15 to 21 mm from the summit of the GT (BV, 62.0 ± 22.7 mm 3 ; BV/TV, 6.1% ± 2.2%; P = .0001 for both). The juxta-articular medial row had the greatest value for both trabecular number (0.3 ± 0.06 mm –1 ; P = .0001) and thickness (0.3 ± 0.08 μm; P = .0001) with the lowest degree of trabecular separation (1.3 ± 0.4 μm; P = .0001). The structure model index (SMI) has been shown to strongly correlate with bone strength, and this was greatest at the inferior-most lateral row 15 to 21 mm from the summit of the GT (2.9 ± 0.9; P = .0001). Conclusion: The inferior-most lateral row, 15 to 21 mm from the tip of the GT, has good bone stock, the greatest cortical thickness, and the best SMI for lateral row anchor placement. The anterior-most part of the GT 15 to 21 mm below its summit had the greatest cortical thickness of all zones. The posterior third of the GT also has good bone stock parameters, second only to the medial row. The best site for lateral row cortical anchor placement is 15 to 21 mm below the summit of the GT. Clinical Relevance: Optimal lateral anchor positioning is 15 to 21 mm below the summit of the greater tuberosity in TOE.